Doing Comparable Worth: Gender, Class and Pay Equity - Cuneo, Carl J. (Labour / Le Travail, 1991)
The article reviews the book, "Doing Comparable Worth: Gender, Class and Pay Equity," by Joan Acker.
Keywords: ACKER; Joan; BOOKS – Reviews; DOING Comparable Worth: Gender; Class & Pay Equity (Book); Discrimination in employment; Nonfiction